PHILOSOPHY OF UKRAINIAN CORDOCENTRIZM - Гнатюк, Я. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In article national specificsty of the Ukrainian philosophy is analyzed/ The basic attention is concentrated on the Ukrainian cordo-centrism which represents historical mentality and intellectual identity of the Ukrainian nation/ the Ukrainian cordo-centrism is considered from different positions: meta-philosophical, historico-philosophical, anthropological, ethical, ontologic, gnosiological and axiologic. Due to such plurality of prospects the essence and specifity of the Ukrainian cordocentrism is established.